Management of Calculus Anuria Using Ureteroscopic Lithotripsy as a First Line Treatment: Its Efficacy and Safety - Savic, Slavisa; Vukotic, Vinka; Lazic, Miodrag; Savic, Natasa (Urology Journal, 2014)
Purpose: To present our experience with emergency ureteroscopic lithotripsy (URSL) for ureteral calculi associated with acute kidney injury (AKI). Materials and Methods: We retrospectively evaluated the 61 patients consisted of 90 ureteral units (UU), who underwent URSL. The cause of anuria was bilateral calculus obstructions in 29 cases, and unilateral calculus obstruction with, absent, nephrectomized contralateral kidney in 32 cases. In the case of bilateral synchronous ureteric calculi same-session bilateral ureteroscopy (SBBU) was done. The duration of anuria varied between 12 to 72 hours. At the end of the procedure, ureteral stent was systematically left in place in all patients. Surgery was performed 6-12 hours after admission to hospital. Patients were followed at least 1 month postoperatively. Results: The stone free rates (SFR) were determined as baseline, on the first post-operative day, and as overall on the 30 days after procedure. The greatest success was achieved in the distal localization of stones up to 10 mm (93%). Renal function returned in 51 (83.6%) patients within 7 days. In 18 (29.5%) patients [18 (20%) UU] we performed second procedure as extracorporeal shockwave lithotripsy in 16.7% and open surgery in 2.2%. In 43 (70.5%) patients URSL was a successful therapeutic approach in dealing with pain, obstruction and calculus. Conclusion: Calculus anuria is a medical emergency that requires rapid diagnosis and prompt treatment for the purpose of decompression. URSL is the proper method of choice for selected patients and can be performed safely and has high success rates with minimal morbidity.